IGF-Binding Proteins in Type-1 Diabetes Are More Severely Altered in the Presence of Complications - Sharma, Ashok; Purohit, Sharad; Sharma, Shruti; Bai, Shan; Zhi, Wenbo; Ponny, Sithara Raju; Hopkins, Diane; Steed, Leigh; Bode, Bruce; Anderson, Stephen W.; She, Jin-Xiong (Frontiers in Endocrinology, 2016)
Aims: Reduced levels of free and total insulin-like growth factor 1 (IGF-I) have been observed in Type-1 Diabetes (T1D) patients. The bioavailability of IGF-I from the circulation to the target cells is controlled by multifunctional IGF binding proteins (IGFBPs). The aim of this study was to profile serum IGFBPs in T1D and its complications. Design: We measured the IGFBP levels in 3662 patient serum samples from our ongoing Phenome and Genome of Diabetes Autoimmunity (PAGODA) study. IGFBP levels of four different groups of T1D patients (with 0, 1, 2, ≥3 complications) were compared with healthy controls. Results: Three serum IGFBPs (IGFBP-1, 2 and 6) are significantly higher in T1D patients and these alterations are greater in the presence of diabetic complications. IGFBP-3 is lower in patients with diabetic complications. Analyses using quintiles revealed that risk of T1D complications increases with increasing concentrations of IGFBP-2 (5th quintile ORs: 18-60, p<10-26), IGFBP-1 (5th quintile ORs: 8-20, p<10-15) and IGFBP-6 (5th quintile ORs: 3-148, p<10-3). IGFBP-3 has a negative association with T1D complications (5th quintile ORs: 0.12-0.25, p<10-5). Conclusions: we found that elevated serum levels of IGFBP-1, 2 and 6 were associated with T1D and its complications and IGFBP-3 level was found to be decreased in T1D with complications. Given the known role of these IGFBPs, the overall impact of these alterations suggest a negative effect on IGF signaling.